The Implementation and Obstacles in Jigsaw Technique in Teaching Reading - Murniati Murniati (English Education Journal, 2015)
This study is intended to figure out the implementation of Jigsaw Technique (JT) in teaching reading to the first year students. The study used a descriptive research design. The population in this study was all the first grade students at SMAN 1 Peusangan Siblah Krueng, a total of 40 students and two English teachers were taken as the sample. The data were collected by using three instruments namely: observation sheets, an interview guide, and a questionnaire. Based on the data analysis, it was found that the two English teachers at the school used JT themselves as a model. Furthermore, the teachers did three phases in using JT, including: (a) preparation, learning curriculum and syllabus: the teachers match the basic competences with appropriate technique. (b) core activities: students’ questions about JT, students are student-centered in the learning process with good interaction, cognitive-affective-psychomotor of the students in using JT are good, (c) closing: summarization of using Jigsaw JT, motivation/moral value and giving homework. In addition, two English teachers did positive performance in using JT. Some difficulties faced by the two English teachers in the implementation of JT in teaching reading are: in designing lesson plan, preparing appropriate teaching materials by using JT, source of reading text. Finally, the students’ responses toward the implementation of using JT were very positive. The findings shows that 90% of the students like to learn reading in English by using JT. So, it is suggested that English teachers should use JT in teaching reading because it is an effective tool in the teaching–learning process.